2013
DOI: 10.1007/s10845-013-0835-x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling pulsed laser micromachining of micro geometries using machine-learning techniques

Abstract: A wide range of opportunities are emerging in the micro-system technology sector for laser micro-machining systems, because they are capable of processing a various types of materials with micro-scale precision. However, few process datasets and machine learning techniques are optimized for this industrial task. This article aims to show how the process parameters of micro-laser milling influence the final features of the microshapes that are produced and aims to identify, at the same time, the most accurate m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 28 publications
1
40
0
1
Order By: Relevance
“…RF has an even greater accuracy of between 33% for the complete dataset and 42% for the uncompleted dataset, with a statistically significant difference in both cases. Considering the standard deviation of the roughness in the dataset, 0.88 μm, the RMSE can be considered a little high (30% for the best model), although still acceptable from the industrial point of view compared with similar works (Bustillo et al 2011a, b;Maudes et al 2017;Teixidor et al 2015). Figure 4 shows the dataset prediction error for each instance (cross size) for the RF model to analyze this fact.…”
Section: Modelingmentioning
confidence: 87%
See 2 more Smart Citations
“…RF has an even greater accuracy of between 33% for the complete dataset and 42% for the uncompleted dataset, with a statistically significant difference in both cases. Considering the standard deviation of the roughness in the dataset, 0.88 μm, the RMSE can be considered a little high (30% for the best model), although still acceptable from the industrial point of view compared with similar works (Bustillo et al 2011a, b;Maudes et al 2017;Teixidor et al 2015). Figure 4 shows the dataset prediction error for each instance (cross size) for the RF model to analyze this fact.…”
Section: Modelingmentioning
confidence: 87%
“…The last two regressors are often used as baseline methods for the purpose of comparison with the naïve approach and the regression model, as stated by previous works on surface roughness (Maudes et al 2017;Teixidor et al 2015). The naïve approach uses the mean value of the output as a prediction that is independent of the input values; in this study, the naïve approach will always predict a surface roughness of 1.20 μm (the mean roughness value considering the whole dataset).…”
Section: Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Pandey and Dubey [19] used pulsed Nd:YAG laser to cut the titanium alloy and showed that lower pulse width and pulse frequency and higher cutting speed result in a better cut. Texidor et al [20] investigated the laser microcutting, and Savriama et al [21] explained the novel pattering effects during the high-frequency laser microcutting of hard ceramics. Jarosz et al [22] presented effect of the cutting speed on the surface roughness and HAZ of stainless steel, while the other control factors were kept constant.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Importantly, the method allows robust integration of various supervised methods, already used in industrial settings, such as (k)Nearest Neighbors ((k)NN) and Random Forest. In particular, the work shows how techniques such as kNN, previously used for roughness modeling elsewhere (Teixidor et al 2015), can be used when partly unlabeled data becomes available.…”
Section: Introductionmentioning
confidence: 99%